Modern operating systems - Tanenbaum, Andrew S., 1944- (New Jersey : Pearson Prentice Hall, 2009)
For Introductory Courses in Operating Systems in Computer Science, Computer Engineering, and Electrical Engineering programs. ' The widely anticipated revision of this worldwide best-seller incorporates the latest developments in operating systems (OS)technologies. The Third Edition includes up-to-date materials on relevant'OS such as Linux, Windows, and embedded real-time and multimedia systems. Tanenbaum also provides information on current research based on his experience as an operating systems researcher. ' Student Resources'Include: * Online Exercises - Provide hands-on experience with building as well as analyzing the performance of OS. In particular, these exercises have been designed to provide experience with analyzing the resource consumptions in Windows and Linux.* Simulation Exercises - Designed to provide experience with building some key components of an OS, including process scheduling, main memory allocation, paging algorithms and virtual memory, and file systems.* Lab Experiments* Please note, GOAL is no longer available with this book. Password-Protected Instructor Resources (Select the Resources Tab to View Downloadable Files): * Power Point Lecture Slides* Figures in both .jpeg and .eps file format* Solutions to Exercises* Please note, GOAL is no longer available with this book. Modern Operating Systems, 3e is the recipient of the Text and Authors Association (TAA) 2010 McGuffey Longevity Award. The McGuffey Longevity Award recognizes textbooks whose excellence has been demonstrated over time.
what is an operating system -- processes and threads -- memory management -- file systems -- input/output -- deadlocks -- multiple processor systems -- security -- case study 1: linux -- case study 2: windows vista -- operating systems design.
Includes bibliographical references (p. 1003-1043) and index.
1
Keywords: CIT; Operating systems (Computers)